In vitro propagation and microtuber induction in Dioscorea belophylla (Prain) Voigt ex Haine - Thankappan, Sreeja; K, Abraham (JOURNAL OF ROOT CROPS, 2015)
A protocol was developed for the in vitro propagation and microtuber induction in Dioscorea belophylla using nodal explants at Central Tuber Crops Research Institute, Thiruvananthapuram, India. MS medium with benzyl adenine (BA) at 3 Î¼M and Kinetin (Kin) at 4 and 5 Î¼M were found to be the best concentrations for developing shoots with good number of nodes and leaves. The addition of 1- naphthaleneacetic acid (NAA) along with cytokinin resulted in healthier leaf production. Among the different concentrations of sucrose tested, MS medium with 4% sucrose was the best for shooting, having the highest shoot length of 11.8 cm and mean number of 17.4 nodes and 11.4 leaves/shoot within 15.4 days of inoculation. Microtuber induction was recorded in the presence of BA (3-5 Î¼M), Kin (3-4 Î¼M) and BA 3 Î¼M along with NAA (1 Î¼M). Addition of 3-8% sucrose in the medium was found to be the best concentration for inducing 1-3 microtubers/culture.